An innovative reputation system for trustworthy and secure vehicle-to-vehicle communication - Almani, Dimah (2025)
Vehicular Ad Hoc Networks (VANETs) are a promising technology that ensures secure and efficient transportation by allowing vehicles to seamlessly communicate with each other and with infrastructure to share real-time information and make better decisions while travelling. However, determining which information is accurate under certain circumstances, such as in the event of an accident, may become challenging when receiving messages from multiple nearby vehicles. Therefore, trusting these messages requires a reliable and secure system to guard against insider attackers, who may intentionally send misleading information, particularly in scenarios without extensive Roadside Units (RSUs) to mediate these exchanges.